1997
DOI: 10.1523/jneurosci.17-12-04895.1997
|View full text |Cite
|
Sign up to set email alerts
|

Chronic Social Stress Alters Levels of Corticotropin-Releasing Factor and Arginine Vasopressin mRNA in Rat Brain

Abstract: In the visible burrow system model of chronic social stress, male rats housed in mixed-sex groups quickly form a dominance hierarchy in which the subordinates appear to be severely stressed. A subgroup of subordinates have an impaired corticosterone response after presentation of a novel restraint stressor, leading to their designation as nonresponsive subordinates. To examine the mechanism underlying the blunted corticosterone response in these animals, in situ hybridization histochemistry was used to quantif… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

9
161
3
10

Year Published

1998
1998
2016
2016

Publication Types

Select...
8
2

Relationship

5
5

Authors

Journals

citations
Cited by 240 publications
(183 citation statements)
references
References 64 publications
9
161
3
10
Order By: Relevance
“…The New England Journal of Medicine hormone messenger RNA in the hypothalamus are abnormally low. 36 Human counterparts with HPA hyporesponsiveness include adults with fibromyalgia 37,38 and chronic fatigue syndrome 39,40 and children with atopic dermatitis. 41 In post-traumatic stress disorder, basal HPA activity is also low, 42,43 although reactivity to stress may not be blunted.…”
Section: Allostasis and Allostatic Loadmentioning
confidence: 99%
“…The New England Journal of Medicine hormone messenger RNA in the hypothalamus are abnormally low. 36 Human counterparts with HPA hyporesponsiveness include adults with fibromyalgia 37,38 and chronic fatigue syndrome 39,40 and children with atopic dermatitis. 41 In post-traumatic stress disorder, basal HPA activity is also low, 42,43 although reactivity to stress may not be blunted.…”
Section: Allostasis and Allostatic Loadmentioning
confidence: 99%
“…Social stress in the VBS produces a variety of changes in neuropeptide and neurochemical systems including altered corticotrophin releasing hormone (CRH) and vasopressin expression [36] and glucocorticoid and mineralocorticoid receptor expression in hippocampus [37]. DOM and SUB also show changes in the serotonin (5-HT) [33,34,38] and dopamine systems [38,39].…”
Section: The Visible Burrow System (Vbs) Model Of Social Stressmentioning
confidence: 99%
“…Such signals are made in the wild as well as in captivity (Mulligan et al, 1994;Grandin, 1998;Panksepp and Burgdorf, 2000;Burgdorf and Panksepp, 2001;Manteuff el et al, 2004;Burman et al, 2007). In fact, it has been found that sound rates, type of calls, and acoustic structure within a call may vary depending on the context of behaviors such as aggression, panic, and social separation (rodents: Goldstein et al, 1996;Albeck et al, 1997;primates: Bayart et al, 1990;Champoux and Suomi, 1994;Friedman et al, 1995;Laudenslager et al, 1995;Boinski et al, 1999;farm animals: von Borell and Ladewig, 1992;Désautés et al, 1997;Weary et al, 1997). Animals living in a controlled environment with predictable daily routines, experience anticipation which is a mental state that can infl uence their behaviors including vocalizations (Krishnamurthy, 1994;Knutson et al, 1998;Burgdorf et al, 2000;Waitt and Buchanan-Smith, 2001;Ulyan et al, 2006;Düpjan et al, 2008;Gilbert-Norton et al, 2009;Polizzi di Sorrentino et al, 2010).…”
Section: Introductionmentioning
confidence: 99%